Exploring the function of Cadherin 13 in Golgi interneurons in the internal granular layer of the cerebellar cortex - Muhd Faris Mohd Kairi (2016)
Members of the cadherin superfamily have been characterized as adhesion molecules with varying functions in different systems. Disruptions to cadherins have been associated to developmental disorders, cancer, and neurological diseases. One of these molecules from this family is Cadherin 13. A mutation or absence of Cadherin 13 within the cerebellum has been linked to Autism Spectrum Disorder (ASD), However, little is known about its precise function within the cerebellum. We have begun to evaluate the function of Cadherin 13 by trying to understand how it affects the morphology of a subtype of cerebellar interneuron, the Golgi cells. To explore the function of Cadherin 13 within the cerebellum, we used conditional knock out mice to study changes in Golgi cells upon deletion of Cadherin 13. Upon deletion of this gene, we found that Golgi cells exhibit reduced number of processes, a lower number of branches emerging from the soma and a general shortening of dendrites and its processes. We hope that this study will provide insight to the function of Cadherin 13 within the cerebellum and its influence in cellular morphology, and reveal a better understanding of how cell adhesion molecules regulate neuronal processes.